Изучение влияния поверхностно-активных веществ на свойства жидкостекольных теплоизоляционных материалов - Рымар, Татьяна Эрнтовна (НТУ "ХПИ", 2017)
Получение блочных теплоизоляционных материалов на основе жидкого стекла с высокими прочностными показателями и низкими плотностью и теплопроводностью возможно лишь при тщательном подборе компонентов смеси. Одним из основных компонентов при получении пеноматериалов является поверхностно-активное вещество, обеспечивающее равномерное распределение газообразующего агента и наполнителя в объеме композиции, и повышающее устойчивость пены. Поэтому представленное в данной работе изучение влияния поверхностно-активных веществ на свойства жидкостекольных теплоизоляционных материалов является достаточно актуальным.

Thermal insulation materials based on liquid glass are of great interest for modern construction. Obtaining block heat-insulating materials with high strength characteristics and low density and thermal conductivity is possible only with careful selection of the components mixture and analysis of all possible nuances in swelling of the liquid-glass composition when processed by temperature or microwave radiation. One of the main components in the production foam materials is a surfactant, which ensures a uniform distribution of the blowing agent and filler in the volume of the composition, and increases the stability of the foam. The role of surfactants in obtaining liquid-glass thermal insulation materials is very important, since without them it is impossible to obtain a structurally homogeneous block with low density and thermal conductivity in combination with high strength. Surfactants help to synchronize the rates of gas formation and solidification of the composition and to achieve its stability until the system acquires a viscosity at which its deformation no longer occurs. Therefore, the study of the effect surfactants on the properties of liquid-glass heat-insulating materials presented in this study is quite relevant.
Study the effect of surfactant on the properties of liquid-glass insulating materials
Keywords: плотность; водопоглощение; влажность сорбционная; предел прочности; изгиб; сжатие; density; water absorption; sorption humidity; bending; compression strength